The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.sbspro.2015.06.153
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Attitudes of Entrepreneurs Towards Entrepreneurship

Abstract: This study develops and uses a scale to identify the innovativeness and positive attitudes of entrepreneurs towards entrepreneurship. The reliability of the scale is found to be high, and based on random sample of 78 entrepreneurs the most and the least innovative characteristics they have and the most and the least positive attitudes they have towards entrepreneurship are revealed. Furthermore, the effects of entrepreneurs' demographic characteristics on these measures are investigated based on hypothesis tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 2 publications
4
21
0
3
Order By: Relevance
“…Moreover, this study also found that two demographic factors, including ethnicity and faculty have a significant impact on the different entrepreneurial attitudes of students. This finding is also in line with Robinson et al [2]; Harris [3] and Gedik [14] who assert that entrepreneurial attitudes will be influenced by some demographic characteristics. Accordingly, to increase the entrepreneurial attitudes, we have to concern with the demographic factors, such as ethnicity and faculty of the students.…”
Section: B Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, this study also found that two demographic factors, including ethnicity and faculty have a significant impact on the different entrepreneurial attitudes of students. This finding is also in line with Robinson et al [2]; Harris [3] and Gedik [14] who assert that entrepreneurial attitudes will be influenced by some demographic characteristics. Accordingly, to increase the entrepreneurial attitudes, we have to concern with the demographic factors, such as ethnicity and faculty of the students.…”
Section: B Discussionsupporting
confidence: 90%
“…According to Karimi et al [13]; Gedik et al [14] and Do and Dadvari [10], there are some demographic factors that may influence the entrepreneurial attitudes, such as gender, ethnicity, educational level, age and field of study. For example, Gedik et al assert that gender has a significant impact on entrepreneurial attitudes [14]. Furthermore, Harris and Gibson argue that parents as entrepreneurs and work experience are also key factors in influencing the entrepreneurial attitudes of students [3].…”
Section: B Demographic Factormentioning
confidence: 99%
“…Sari's research results also shows the existence of both directly or indirectly influence between attitudes toward entrepreneurship behavior of students at the University of Education Ganesha [22]. The results of Gedik also yield the same conclusions as this research [4]. 4.…”
Section: There Is Influence Between Entrepreneurship Learning On Entrsupporting
confidence: 76%
“…The results of other studies show that there is an influence between entrepreneurial attitudes toward entrepreneurial behavior. Result of research of Gedik, et al explain there is influence between entrepreneurship attitude toward entrepreneurship behavior [4].…”
Section: Introductionmentioning
confidence: 99%
“…Los siguientes estudios consideran que las características de los directivos de las empresas logran explicar cómo ellos superan las limitaciones que se presentan en los procesos de internacionalización: Aaby y Slater (1989), Coviello y Munro (1997), Madsen y Servais (1997), Westhead et al (2001), Oviatt y McDougall (2005), Kuivalainen et al (2007), Acedo y Jones (2007), Laanti et al (2007), Karra et al (2008), Kim y Hemmert (2016). Dichas características tales como la experiencia internacional, edad, género, idioma, educación, permiten que el empresario desarrolle estrategias globales que permiten reconocer las oportunidades del mercado (Jolly et al, 1992;Fillis, 2001;Leonidou et al, 1998, Gedik et al, 2015, Francioni et al, 2015Laguir y Den Bester, 2016). Por lo tanto, las experiencias y habilidades del emprendedor explican el comportamiento empresarial y conducen a un desempeño exportador exitoso al brindar mayor conocimiento a la empresa (Storey, 1994;Escandón y Hurtado, 2012).…”
Section: Características Del Emprendedor Y Postura Emprendedoraunclassified